Hormonal contraceptive exposure relates to changes in resting state functional connectivity of anterior cingulate cortex and amygdala - Hidalgo-Lopez, Esmeralda; Noachtar, Isabel; Pletzer, Belinda (Frontiers in Endocrinology, 2023)
Hormonal contraceptives (HCs), nowadays one of the most used contraceptive methods, downregulate endogenous ovarian hormones, which have multiple plastic effects in the adult brain. HCs usually contain a synthetic estrogen, ethinyl-estradiol, and a synthetic progestin, which can be classified as androgenic or anti-androgenic, depending on their interaction with androgen receptors. Both the anterior cingulate cortex (ACC) and the amygdala, express steroid receptors and have shown differential functionality depending on the hormonal status of the participant and the use of HC. In this work, we investigated for the first time the relationship between ACC and amygdala resting state functional connectivity (rs-FC) and HC use duration, while controlling for the progestin androgenicity. A total of 231 healthy young women participated in five different magnetic resonance imaging studies and were included in the final analysis. The relation between HC use duration and i) gray matter volume, ii) fractional amplitude of low-frequency fluctuations and iii) seed-based connectivity during resting state in the amygdalae and ACC was investigated in this large sample of women. In general, rs-FC of the amygdalae with frontal areas, and between the ACC and temporoparietal areas, decreased the longer the HC exposure and independently of the progestin’s androgenicity. The type of HC’s progestin did show a differential effect in the gray matter volume of left ACC and the connectivity between bilateral ACC and the right inferior frontal gyrus.